1999
DOI: 10.1007/s004210050538
|View full text |Cite
|
Sign up to set email alerts
|

Inspiratory muscle adaptations following pressure or flow training in humans

Abstract: Skeletal muscle adapts differently to training with high forces or with high velocities. The effects of these disparate training protocols on the inspiratory muscles were investigated in ten healthy volunteers. Five subjects trained using high force (pressure) loads (pressure trainers) and five trained using high velocity (flow) loads (flow trainers). Pressure training entailed performing 30 maximal static inspiratory efforts against a closed airway. Flow training entailed performing 30 sets of three maximal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
18
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…The main finding was the increase in PO due to a larger V 'I as well as to a reduction in tI and tI/ttot with a normal VT. These results, which are in agreement with data from TZELEPIS et al [16] and BISSCHOP et al [17], suggesting changes in shortening velocity of in-spiratory muscles, allow us to speculate upon structural changes at the level of muscle fibres in response to specific recruitment patterns induced by training.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The main finding was the increase in PO due to a larger V 'I as well as to a reduction in tI and tI/ttot with a normal VT. These results, which are in agreement with data from TZELEPIS et al [16] and BISSCHOP et al [17], suggesting changes in shortening velocity of in-spiratory muscles, allow us to speculate upon structural changes at the level of muscle fibres in response to specific recruitment patterns induced by training.…”
Section: Discussionsupporting
confidence: 92%
“…In conclusion, the results of the present study, as well as those reported by others in normal subjects [3,16] suggest that the use of moderate loads to train inspiratory muscles elicits improvements in both strength and shortening velocity and thus, in power output. We believe that in patients with chronic obstructive pulmonary disease, these outcomes are more relevant for coping with the increased ventilatory demands of daily life activities, than the improvement in strength alone achieved by training with high pressure loads [1].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…There is very little information on the effect of inspiratory muscle conditioning on inspiratory flow, and thus on inspiratory muscle PO. As with other skeletal muscles, it has been shown that the inspiratory muscles can be trained to increase their capacity to generate force (pressure) or muscle shortening velocity (flow) (Leith and Bradley 1976;Tzelepis et al 1999;Tzelepis et al 1994). During swimming (flow-targeted type training) a higher tidal volume may cause encroachment on end-inspiratory reserve volume, which requires the inspiratory muscles to shorten at a high velocity during the rapid inspiration as the face leaves the water (Cordain and Stager 1988;Fanta et al 1983).…”
Section: Respiratory Muscle Functionmentioning
confidence: 99%
“…During swimming (flow-targeted type training) a higher tidal volume may cause encroachment on end-inspiratory reserve volume, which requires the inspiratory muscles to shorten at a high velocity during the rapid inspiration as the face leaves the water (Cordain and Stager 1988;Fanta et al 1983). Tzelepis et al (Tzelepis et al 1999) found that flow-targeted training diminished the time to reach the peak oesophageal pressure by about 25%, when performing IMT. Thus, during swimming, it is feasible that the enhanced airway resistive load due to high flow rates during inspiration and expiration (Courteix et al 1997;Kohl et al 1997) increases strength and shortening velocity of the inspiratory muscles, and thus, in PO.…”
Section: Respiratory Muscle Functionmentioning
confidence: 99%